Relocating the Conflict Between Science and Religion at the Foundations of the History of Science - Ungureanu, James C. (Zygon, 2018)
Historians of science and religion usually trace the origins of the conflict thesis, the notion that science and religion have been in perennial conflict or warfare, to the late nineteenth century, particularly to the narratives of New York chemist John William Draper and historian Andrew Dickson White. In this essay, I argue against that convention. Their narratives should not be read as stories to debunk, but rather as primary sources reflecting themes and changes in religious thought during the late nineteenth century. I contend that Draper and White were part of a long liberal Protestant heritage that emphasized history, reason, and religious emancipation against ecclesiastical authority. As an alternative source of origins, however, I suggest that the real conflict thesis is to be found in the fledgling discipline of the history of science as it emerged during the late nineteenth and first half of the twentieth century. The real origin of the conflict thesis is found in the very discipline that now seeks to condemn it.